Leading Organizational Cultural Competency: Nurse Leader Rounds and Care for Diverse Patients. (December 2016) - Ogbolu, Yolanda; Scrandis, Debra A.; Fitzpatrick, Grace; Newhouse, Robin
Abstract : Chief nurse executives (CNEs) face challenges in providing high-quality, patient-centered care for diverse populations. Although the implementation of culturally and linguistically appropriate services (CLAS) may improve patient satisfaction, the cost of initiatives and education coupled with shortened episodes of care pose obstacles. The article describes themes from a qualitative study with CNEs, describes resources and best practices, and highlights nurse leader rounds as a vehicle for implementing CLAS.